Arthroscopic synovectomy with loose bodies removal in a case of synovial chondromatosis of knee joint - B., Karthik; Palanivelrajan; Sharma, B. P.; Jain, Vineeth; Lal, Hitesh; S., Vishnu (International Journal of Research in Orthopaedics, 2025)
Synovial chondromatosis is a rare condition which affects the synovial joints, tendon sheath, bursa. Mostly commonly seen in 3rd to 5th decade with male predominance. The exact etiology is unknown. usually manifest clinically as synovitis. Clinical evaluation with appropriate radiological evaluation is necessary for the diagnosis. Surgical intervention is appropriate either open or arthroscopic. It involves arthrosopic loose body removal with extensive synovectomy. Histopathological evaluation is required for confirmation of diagnosis. Long term follow up is needed